Cytomegalovirus (CMV) infection and pregnancy-potential for improvements in Australasian maternity health providers' knowledge. (2nd October 2018) - Shand, A. W.; Luk, W.; Nassar, N.; Hui, L.; Dyer, K.; Rawlinson, W.
Abstract: Purpose: To assess the knowledge, practice and attitudes of maternity clinicians regarding congenital cytomegalovirus (CMV). It is the most common congenital infection, and well-recognized cause of neurodevelopmental disability and hearing loss. New consensus recommendations state all pregnant women and health-care providers should be educated about congenital CMV infection and preventive measures. Materials and methods: An email questionnaire was distributed in October 2015 to specialists, diplomates (general practitioners), and trainees of the Royal Australian New Zealand College of Obstetricians and Gynaecologists (RANZCOG), and Victorian and New South Wales midwives. Results: 774 responded: (37.3% specialists, 17.3% diplomates, 16.8% trainees, 28.6% midwives). Clinicians had variable knowledge of fetal sequelae, transmission routes and prevention. Overall, 30.2% felt confident about discussing CMV in pregnancy: less than 10% of midwives (7.4%) and less than half of specialists (47.1%, p  < .0001). Only 8.8% of respondents routinely discussed CMV prevention with pregnant women. The majority (69.3%) responded that professional societies should make practice recommendations, and 88% thought more patient information was needed, preferably leaflets. Conclusions: Australasian maternity clinicians lack confidence and knowledge about congenital CMV. Few (<10%) routinely provide advice on prevention. There is urgent need for clinical guidance and patient information to reduce the burden of disease.